2019
DOI: 10.1007/s10329-019-00769-2
|View full text |Cite
|
Sign up to set email alerts
|

Primate thanatology and hominoid mortuary archeology

Abstract: In recent years, a thanatology of primates has become a respectable research topic, and although still sparse, observations among several taxa have shown how complex responses to the dead can be. In human evolutionary archeology, re-analysis of old 'burial' sites is slowly revising our view on the development of specifically human responses to the dead. We propose here the means of integrating information from the two disciplines of primatology and archeology, in support of the field of primate thanatology. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Experience is likely to play an important role, but we lack information about how individual understanding may change with repeated exposures to sick, unconscious, dying or dead conspecifics (Stewart et al 2012;Anderson 2018;Gonçalves & Biro 2018;Monsó 2020). Most of our conclusions are based on indirect evidence, and much remains to be investigated about primate responses to death (Pettitt & Anderson 2020). The experimental study of the cognitive abilities of monkeys and great apes will undoubtedly provide valuable insights into their capacity for abstraction and the clues they can use to recognize animacy and agency (Brosnan & Vonk 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experience is likely to play an important role, but we lack information about how individual understanding may change with repeated exposures to sick, unconscious, dying or dead conspecifics (Stewart et al 2012;Anderson 2018;Gonçalves & Biro 2018;Monsó 2020). Most of our conclusions are based on indirect evidence, and much remains to be investigated about primate responses to death (Pettitt & Anderson 2020). The experimental study of the cognitive abilities of monkeys and great apes will undoubtedly provide valuable insights into their capacity for abstraction and the clues they can use to recognize animacy and agency (Brosnan & Vonk 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Several authors have argued, based on a limited number of cases, that individuals react differently to deceased partners depending on the cause of death, but the views expressed by these authors are conflicting. According to Anderson and collaborators (Anderson 2011;Yang et al 2016;Pettitt & Anderson 2020), sudden and traumatic deaths resulting from an accident or a killing would trigger more alarm and violent behaviours than deaths due to non-apparent causes such as illness. In contrast, Boesch (2012) proposes that bodies with wounds generate fewer signs of fear and alarm in chimpanzees than those of individuals who die from unexplained causes such as illness.…”
Section: Awareness Of Mortalitymentioning
confidence: 99%
“…Attentive thanatological behaviours may thus have evolved in different social animals as a by-product of strong social bonds through parallel evolution and/or phylogenetic continuity [69]. If so, it is possible that early human mortuary practices arose as an extension of primates' attentive thanatological behaviour [70].…”
Section: Discussionmentioning
confidence: 99%
“…These behaviours are interpreted as epimeletic, meaning relating to altruistic behaviour towards an injured animal, mostly described in dolphins [81][82][83][84][85][86][87]. Epimeletic behaviours in animals are maybe the most adequate behaviours to study anthropomorphism as these behaviours are very rarely observed and impossible to test (we will not deliberately injure or kill an individual to assess whether its congeners will save it), and finally, researchers have very little knowledge of the underlying beliefs and mental states of death or fear of death in animals [88][89][90][91]. So, only experts on this topic can answer the questions and answer correctly, while the majority of people display anthropomorphism.…”
Section: Introductionmentioning
confidence: 99%